2018
DOI: 10.1371/journal.pone.0201824
|View full text |Cite
|
Sign up to set email alerts
|

Early stop of progesterone supplementation after confirmation of pregnancy in IVF/ICSI fresh embryo transfer cycles of poor responders does not affect pregnancy outcome

Abstract: Previous studies indicated that progesterone can be withdrawn at the time of the first positive β-hCG test without compromising the clinical pregnancy outcome in normal ovarian responder. However, the effect of early stop of progesterone supplementation for patients with poor ovarian response (POR) has not been investigated. This study retrospectively collected data from patients with POR in 156 IVF/ICSI fresh embryo transfer (ET) cycles in single tertiary center from January 2010 to June 2016. All the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Aboulghar and colleagues conducted a research in which patients were indided to either continue or discontinue receiving progesterone when there was fetal heart with ultrasound, and found comparable outcomes between the groups, indicating that continuing progesterone beyond this time has no benefit [ 78 ]. In addition, several studies have found no difference in pregnancy outcome and suggested that progesterone supplement would be safely discontinued after the first test for positive β-hCG [ 84 , 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aboulghar and colleagues conducted a research in which patients were indided to either continue or discontinue receiving progesterone when there was fetal heart with ultrasound, and found comparable outcomes between the groups, indicating that continuing progesterone beyond this time has no benefit [ 78 ]. In addition, several studies have found no difference in pregnancy outcome and suggested that progesterone supplement would be safely discontinued after the first test for positive β-hCG [ 84 , 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone production in early pregnancy is therefore normal in fresh transfer ART. Several investigators have documented that progesterone supplementation can be stopped on the day of the positive pregnancy test [5,6] without risking an increase in the rate of pregnancy losses. Most groups, however, continue progesterone treatment for further weeks-often 10 weeks, but without good reason.…”
Section: Fresh Embryo Transfersmentioning
confidence: 99%
“…Miscarriage rate was similar for both study groups. In addition, several retrospective cohort studies have failed to demonstrate any benefit of extended LPS administration (11)(12)(13).…”
Section: Review Of the Literaturementioning
confidence: 99%